Comparing Meaning in Life, Cognitive Emotion Regulation and Body Image Concern among Women with and without Postpartum Depression - Shakib Haji Agha, Rana; Kachooei, Mohsen (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Postpartum depression causes negative changes in mothers’ mood and family cohesion, undermines adjustment of mothers with their children, and prevents children from forming a healthy relationship with their mothers. The purpose of this study was to compare meaning in life, strategies of cognitive emotion regulation and body image concern in women with and without postpartum depression. Methods: In this causal-comparative research, participants were selected by convenience sampling among women in the postpartum period in Tehran in 2021. Data was gathered using the Edinburgh Postpartum Depression Scale, Meaning in Life Questionnaire, Cognitive Emotion Regulation Questionnaire, and body image concern inventory. Then, 82 women with postpartum depression and 82 without postpartum were analyzed using ANOVA and MANOVA tests in SPSS-21. Results: There is a meaningful difference between two groups (women with and without postpartum depression) in terms of presence subscale in meaning in life questionnaire, non-adaptive strategies of cognitive emotion regulation scale except for self-blame subscale and adaptive strategies of cognitive emotion regulation except for acceptance sub-scale, and body image concern (p<0.05). In fact, depressed women use more non-adaptive strategies and suffer more from body image concern. However, presence of meaning in life and use of adaptive strategies are less prevalent among these depressed women. Conclusions: Taken together, the findings shed light on the importance of meaning in life, cognitive emotion regulation and body image concern in postpartum depression and highlight potential targets for developing interventions in order to prevention and treatment of postpartum depression.